Effect of Eu doping on the thermoluminescence of UV and gamma irradiated Mg2B2O5 nanophosphors. (2nd February 2022) - Kumar, Jitender; Kumar, Shalendra; Shekhar, Chander; Brajpuriya, Ranjeet; Vij, Ankush
Abstract: This article presents the effect of europium (Eu) doping on the thermoluminescence (TL) of ultraviolet (UV‐254 nm) and gamma irradiated triclinic Mg2 B2 O5 nanophosphors. The diffuse reflectance predicts slight decrease in band gap from 5.18 to 4.99 eV with increasing Eu (1%, 3%, and 5%) content in Mg2 B2 O5 . The TL glow curves of UV irradiated samples comprised of a main peak around 500 K with weak intensity peak/shoulders in low temperature region. Interestingly Eu (3%) doped Mg2 B2 O5 shows maximum TL intensity with suppression of low temperature shoulder peaks and almost linear UV dose dependent TL response. However, in the case of gamma irradiated Eu (1% and 3% doped) samples, TL glow curve comprises of a main peak around 425–445 K and closely lying peak around 500–515 K with relatively lesser intensity. In case of Eu (5%) doped samples, TL peak around 508 K starts dominating over peak around 425 K. TL of both UV and gamma irradiated samples showed the presence of various deep and shallow defect states within the bandgap of materials having different kinetic parameters, which were determined using TLanal software based on Kiti's general order equation. The present study shows that Eu doped Mg2 B2 O5 nanophosphors can be tuned for UV and gamma dosimetry. Abstract : Eu doped Mg2B2O5 exhibits highly responsive TL for both UV and gamma rays. Eu (3%) doped sample showed optimized TL response for UV and almost linear UV dose‐dependent TL response; however, gamma‐induced TL shows interplay of peak intensities with Eu content and gamma dose. TL analysis showed the presence of various deep and shallow defects The present study shows that Eu doped Mg2B2O5 nanophosphors can further be tuned for UV and gamma dosimetry.